Ultrathin MoS2 Nanosheets Supported on N‐doped Carbon Nanoboxes with Enhanced Lithium Storage and Electrocatalytic Properties. Issue 25 (4th May 2015) - Yu, Xin‐Yao; Hu, Han; Wang, Yawen; Chen, Hongyu; Lou, Xiong Wen (David)
Abstract Molybdenum disulfide (MoS2) has received considerable interest for electrochemical energy storage and conversion. In this work, we have designed and synthesized a unique hybrid hollow structure by growing ultrathin MoS2 nanosheets on N‐doped carbon shells (denoted as C@MoS2 nanoboxes). The N‐doped carbon shells can greatly improve the conductivity of the hybrid structure and effectively prevent the aggregation of MoS2 nanosheets. The ultrathin MoS2 nanosheets could provide more active sites for electrochemical reactions. When evaluated as an anode material for lithium‐ion batteries, these C@MoS2 nanoboxes show high specific capacity of around 1000 mAh g−1, excellent cycling stability up to 200 cycles, and superior rate performance. Moreover, they also show enhanced electrocatalytic activity for the electrochemical hydrogen evolution.